Planning in Athletes with Physical Motor Disabilities, Bullet-Impulsion Amputees - M.J. Perna Riera; J.F. Monteagudo Soler (Editura Universitatii Transilvania din Brasov, 2023)
Contemporary training is not based on experiences, its success lies in the confluence of knowledge and application of the different sciences that converge in it. The objective of the research was to argue what aspects should be considered for sports planning in athletes with physical motor disabilities, bullet amputees. Descriptive research is carried out. Arguing their different classes and classifications and the aspects to take into account when planning training. Provincial and national coaches and managers collaborated as a sample. Research methods were used such as analysis and synthesis, survey, interview, and document analysis, which made it possible to define the essential elements for a correct individualization of the training.